An Analysis of Illocutionary Acts through the Character of Edmund Pevensie in “The Chronicles of Narnia: The Lion, The Witch, and The Wardrobe” Novel - Yuradana, Zennia Laouisa (Dinamika Bahasa dan Budaya, 2025)
The objective of this research is to identify the types and the most dominant type of illocutionary acts used by the character of Edmund Pevensie in the novel The Chronicles of Narnia: The Lion, the Witch, and the Wardrobe. This study employed John Searle's theory of illocutionary acts. According to this theory, illocutionary speech acts are categorized into five types: assertive, directive, commissive, expressive, and declarative. A qualitative descriptive method was utilized in this research, with observation as the instrument and data tables for analysis. The data collected consisted of utterances made by the character Edmund Pevensie to examine the types of illocutionary acts. Based on the research findings, the researcher found 64 assertive utterances, 38 directive utterances, 8 commissive utterances, and 5 expressive utterances. Subsequently, a percentage calculation was conducted for the identified types. The results showed that 56% were assertive, 33% were directive, 7% were commissive, and 4% were expressive. Then, based on the analysis the most dominant type used by Edmund is the assertive type. Keywords: speech acts, illocutionary acts, Narnia novel, Edmund Pevensie